(untitled) - Kottak, Conrad Phillip (Boston, 2006)
This text offers an introduction to the five subdisciplines of anthropology: cultural, physical, archaeological, anthropological linguistics and applied anthropology. To reflect the role of anthropology in today's world, Professor Kottak has revised both the content and the organization of the text in a way which gives the students a balanced introduction to anthropology and its relevance. The special theme of this edition is "Preserving Cultural Diversity in the Face of Globalization". Two new chapters - "Ethnicity and Ethnic Relations" and "Cultural Exchange and Survival" - explore the significance of the demise of the Soviet Union and world-wide ethnic conflicts, as well as multiculturalism in the US and Canada, and cultural survival globally.
Keywords: Anthropology,Nhân loại học